(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
According to our previous works on cellulose Iβ and Iα, the weak interactions, though easily ignored, play certain role in the stability mechanism of nature cellulose. These weak interactions should never be ignored or underestimated. In this work, a molecular dynamics study of cellulose Iα was reported to evaluate the weak interactions under various temperatures. The polar and non-polar solvation interactions and hydrogen bonding were taken into account. The Van der Waals, electrostatic, polar solvation and non-polar solvation energy per chain were estimated up to −131.68, −56.38, 29.16 and −41.76 Kcal/mol at room temperature. The weak interactions behaviors of cellulose Iα, including that of the cellulose Iβ and Iα reported previously, were compared. The results indicate that hydrogen bonding contribute obviously for the intrachain stability. The interchain electrostatic interaction maintain a reasonable level under 300 K but decreases rapidly with the ascending of temperature. The polar and non-polar solvation interaction plays an important role not only to interchain under high temperature but also to the intersheet stability. In addition, the hydrogen bonding in intersheet is weaker than that of intrachain and interchain. The result is same as cellulose Iβ that relatively weak hydrogen bonding and strong nonbonded interactions keep the intersheet stability collaboratively.